EFEKTIVITAS PENGGUNAAN EDMODO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SISTEM KOMPUTER KELAS X MULTIMEDIA SMK MANBA’UL ‘ULUM - M. Agri Triansyah; Siti Sarah Zafira (PERISKOP : Jurnal Sains dan Ilmu Pendidikan, 2021)
This study aims to determine the difference between the learning outcomes of class X Multimedia students in Computer Systems subjects using conventional methods with students using Edmodo learning media at SMK Manba'ul 'Ulum, knowing the effectiveness of Edmodo on student learning outcomes in Computer Systems subjects at SMK Manba'ul 'Ulum. This research uses a questionnaire method with a Likert scale on 37 students of SMK Manba'ul 'Ulum as the population. The purpose of using a questionnaire in this study was to determine student responses after using Edmodo media on computer systems subjects. The results of this study were obtained the percentage of students in the use of Edmodo learning media in the high category of 8% with 3 respondents, while the medium category was 38% with 14 respondents, in the low category of 35 with 13 respondents, and in the very category low at 19% with a total of 10 respondents. This classification is based on the standardization of the Ideal Mean (MI) and Ideal Standard Deviation (SDi) values. The level of use of Edmodo learning media in class X MM 1 SMK Manba'ul 'Ulum Cirebon is in the medium category. Where, the level of activeness of class X MM1 students at SMK Manba'ul 'Ulum in accessing Edmodo was only 77.3% and another 22.7% were less active and passive towards Edmodo. It can be concluded that the level of use of Edmodo learning media in the high category is 8%, the medium category is 38%, the low category is 35%, and the very low category is 19%. The existence of the influence of Edmodo learning media with significant student learning outcomes, this is evident from the average results of the questionnaire of 76.22.